332 Innovative strategies to reduce traffic related injuries and deaths in youth. (1st September 2016) - Banfield, Joanne; Redelmeier, Donald
Abstract : Background: Road traffic injuries are the leading cause of death among young people, aged 15–29 years. Studies have shown young drivers are more likely to underestimate the probability of specific risks caused by traffic situations, as well as to overestimate their own driving skills making them more vulnerable to trauma. The P.A.R.T.Y. (Prevent Alcohol and Risk-Related Trauma in Youth) Program, developed in 1986 is a one day, in hospital injury awareness and prevention program for youth aged 15 and older. The goal is to provide young people with information about trauma that will enable them to recognise their injury risks, make prevention-oriented choices and adopt behaviours that minimise unnecessary risks through vivid clinical reality. Methods: Several research studies have been undertaken to determine effectiveness and changes in attitudinal risk behaviour from youth attending the P.A.R.T.Y. A ten-year longitudinal study was conducted to determine whether students who attended P.A.R.T.Y. had a reduction in injuries compared with a matched control group of students based on age, gender and geographic area who did not attend the program. Students follow the course of injury from occurrence through transport, treatment, rehabilitation and community re-integration phases. Additionally by augmenting a didactic format through a technologically innovative approach including but not limited to vivid clinical reality, social media, interactive websites and simulators we see attitudinal and behavioural changes. Results: The 10 year longitudinal study showed P.A.R.T.Y. participants had a lower incidence of traumatic injuries than a control group of non-P.A.R.T.Y. participants of the same age, gender, residential area, and initial year in database, during the 10-year study. Conclusions: Research-driven, psycho-social theories of behaviour and technologically innovative approaches have proven it is possible to influence behaviour through the delivery of well-designed and well-executed road safety strategies, programs and campaigns. Providing students with real-life education to depict the vivid clinical reality of injuries was shown to be a compelling and effective method of education.